IMPLEMENTASI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DALAM PEREDARAN KOSMETIK YANG MENGANDUNG BAHAN KIMIA BERBAHAYA - Siti Mahmudah*), Hasna Maulida, Srie Wiletno, (Diponegoro Law Journal, 2013)
Nowadays, many cosmetic products contain hazardous materials spreading on the market resulting in consumers’ deprivation. One of those products is mercury. In relation to the released products, Indonesia has enacted Law No. 8 of 1999 on Consumer Protection. The issue that has been put under investigation is a legal protection form for consumers based on Law No. 8 of 1999 on Consumer Protection, controlled by BPOM Semarang as the agency that oversees drugs and foods, as well as the constraints dealt by BBPOM Semarang in carrying out the surveillance. Research has entitled an Implementation of Law No. 8 of 1999 on Consumer Protection in the Distribution of Cosmetics Containing Hazardous Chemicals uses juridical-empirical approach. Research shows that UUPK has provided safeguards for the rights of consumers which regulated in Article 4 UUPK, UUPK even provides institutions to resolve arisen disputes, followed by the issuance of Presidential Decree number 203 of 2001 which set the BPOM as Non Government Institutions Department (LPMD), in actual BBPOM Semarang as POM’s Technical Implementation Unit in Central Java also monitors the pre-market surveillance in the means of production, which contains notification at this stage, as well as the post-market surveillance in order to monitor the quality of distribution facilities of cosmetic products that have been circulating in the market, but in practice BBPOM Semarang experience different constraints from both BBPOM Semarang itself (internal) and Community (external).